Gamified digital exercises to enhance reading literacy in Kazakhstani primary schools - Akkalam Zhekeyeva; Aziya Zhumabayeva; Aktoty Akzholova; Gulbanu Saduakas; Magripa Ibrayeva; Dinara Sambet (Institute of Advanced Engineering and Science, 2026)
Recent national and international large-scale assessment results indicate persistent difficulties in higher-order reading comprehension among Kazakhstani primary school students. Although reading literacy (RL) is a strong predictor of academic success, existing instructional practices do not consistently support the development of advanced comprehension skills, and empirical evidence on technology-supported reading instruction in the Kazakh-language context remains limited. This study evaluated a technology-enhanced instructional framework integrating curriculum-aligned gamified digital exercises (GDE) into Grade 4 Kazakh language lessons. A quasi-experimental pre-test/post-test control group (CG) design was employed with 100 fourth-grade students. The experimental group (EG) participated in a six-week intervention implemented under typical classroom information and communication technologies (ICT) constraints, while the CG received traditional instruction. The results demonstrated significantly greater improvements in overall RL in the EG, with large effect sizes, particularly in higher-order comprehension tasks involving inference and information integration. A strong positive correlation was found between gains in RL and reading motivation. These findings suggest that curriculum-aligned gamified digital activities can effectively enhance both cognitive and motivational dimensions of reading development in resource-constrained primary education settings.